Multisensory integration enhances audiovisual responses in the Mauthner cell - Santiago Otero-Coronel; Thomas Preuss; Violeta Medan (eLife)
Multisensory integration (MSI) combines information from multiple sensory modalities to create a coherent perception of the world. In contexts where sensory information is limited or equivocal, it also allows animals to integrate individually ambiguous stimuli into a clearer or more accurate percept and, thus, react with a more adaptive behavioral response. Although responses to multisensory stimuli have been described at the neuronal and behavioral levels, a causal or direct link between these two is still missing. In this study, we studied the integration of audiovisual inputs in the Mauthner cell, a command neuron necessary and sufficient to trigger a stereotypical escape response in fish. We performed intracellular recordings in adult goldfish while presenting a diverse range of stimuli to determine which stimulus properties affect their integration. Our results show that stimulus modality, intensity, temporal structure, and interstimulus delay affect input summation. Mechanistically, we found that the distinct decay dynamics of FFI triggered by auditory and visual stimuli can account for certain aspects of input integration. Altogether, this is a rare example of the characterization of MSI in a cell with clear behavioral relevance, providing both phenomenological and mechanistic insights into how MSI depends on stimulus properties.